Acutely increasing δGABAA receptor activity impairs memory and inhibits synaptic plasticity in the hippocampus - Whissell, Paul D.; Eng, Dave; Lecker, Irene; Wang, Dian-Shi; Martin, Loren J.; Orser, Beverley A. (Frontiers in Neural Circuits, 2013)
Extrasynaptic γ-aminobutyric acid type A (GABAA) receptors that contain the δ subunit (δGABAA receptors) are expressed in several brain regions including the dentate gyrus (DG) and CA1 subfields of the hippocampus. Drugs that increase δGABAA receptor activity have been proposed as treatments for a variety of disorders including insomnia, epilepsy and chronic pain. Also, long-term pretreatment with the δGABAA receptor–preferring agonist 4,5,6,7-tetrahydroisoxazolo[5,4-c]pyridin-3-ol (THIP) enhances discrimination memory and increases neurogenesis in the DG. Despite the potential therapeutic benefits of such treatments, the effects of acutely increasing δGABAA receptor activity on memory behaviors remain unknown. Here, we studied the effects of THIP (4 mg/kg, i.p.) on memory performance in wild-type (WT) and δGABAA receptor null mutant (Gabrd–/–) mice. Additionally, the effects of THIP on long-term potentiation (LTP), a molecular correlate of memory, were studied within the DG and CA1 subfields of the hippocampus using electrophysiological recordings of field potentials in hippocampal slices. The results showed that THIP impaired performance in the Morris water maze, contextual fear conditioning and object recognition tasks in WT mice but not Gabrd–/– mice. Furthermore, THIP inhibited LTP in hippocampal slices from WT but not Gabrd–/– mice, an effect that was blocked by GABAA receptor antagonist bicuculline. Thus, acutely increasing δGABAA receptor activity impairs memory behaviors and inhibits synaptic plasticity. These results have important implications for the development of therapies aimed at increasing δGABAA receptor activity.